Adab Based Regulation of Academic Anxiety: Reframing University Student Learning through Al-Attas’s Ta’dib Paradigm - Hanifiyatus Samhah; Mohammad Zakki Azani; Muhammad Wildan Shohib (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines the application of the ta'dib paradigm from Syed Muhammad Naquib al-Attas in overcoming academic anxiety among college students. Academic anxiety is often a barrier that affects students' emotional well-being and academic performance. Although considered part of the learning process, poorly managed anxiety can adversely affect the quality of learning. The ta'dib paradigm, which integrates intellectual, moral, and spiritual aspects, offers a holistic approach to education that can create a balance between academic achievement and students' emotional well-being. Through this adab-based approach, students are taught to manage anxiety, build good character, and maintain a balance between academic pressure and emotional management. This research shows that the application of ta'dib can create a healthier and more supportive educational environment, as well as help students manage academic anxiety more effectively. The study also proposes the need to integrate moral and spiritual aspects in higher education to create individuals who are balanced and able to face academic challenges more calmly.